Proceedings of the 23rd Annual Conference on Computer Graphics and Interactive Techniques 1996
DOI: 10.1145/237170.237284
|View full text |Cite
|
Sign up to set email alerts
|

Adding force feedback to graphics systems

Abstract: Integrating force feedback with a complete real-time virtual environment system presents problems which are more difficult than those encountered in building simpler forcefeedback systems. In particular, lengthy computations for graphics or simulation require a decoupling of the haptic servo loop from the main application loop if high-quality forces are to be produced. We present some approaches to these problems and describe our force-feedback software library which implements these techniques and provides ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
105
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 201 publications
(105 citation statements)
references
References 17 publications
1
105
0
Order By: Relevance
“…The goal of haptic rendering is to enable a user to touch, feel, and manipulate virtual objects through haptic interfaces as realistically as possible (Mark et al, 1996), (Ruffaldi et al 2006). A force-feedback device can generate kinesthetic information and temporal tactile information.…”
Section: A Haptic Renderingmentioning
confidence: 99%
“…The goal of haptic rendering is to enable a user to touch, feel, and manipulate virtual objects through haptic interfaces as realistically as possible (Mark et al, 1996), (Ruffaldi et al 2006). A force-feedback device can generate kinesthetic information and temporal tactile information.…”
Section: A Haptic Renderingmentioning
confidence: 99%
“…Theses approaches are typically used for single point of contact haptic interaction with rigid objects. Adachi et al used a plane that always tangent to the virtual object surface (Adachi et al, 1995), as an intermediate representation, as did Mark et al in (Mark et al, 1996). Balaniuk in (Balaniuk et al, 1999) used a spherical local model.…”
Section: Haptic Rendering With Deformable Objectsmentioning
confidence: 99%
“…It has been clearly shown that it is necessary to run the simulation and the graphics loops of virtual environments (VE) systems asynchronously in order to maintain reasonable display update rates (around 30Hz) in the presence of long simulation computation. Such a decoupling is even more critical for force display, where high update rate is required to produce high-quality forces (Gossweiler et al, 1993) (Adachi et al, 1995) (Mark et al, 1996) (Balaniuk, 1999). We can decouple the simulation and haptic loops on a single machine by using multiple processes (Adachi et al, 1995) (Balaniuk, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Early integrated systems include Project GROPE [3], the Nanomanipulator [17], and the Nanobench [8]. These projects focused on rendering aspects of molecular dynamics, drug docking simulations, and real-time interactions with a scanned-probe microscope.…”
Section: Previous Workmentioning
confidence: 99%